Incidence of malunion in displaced supracondylar fracture of humerus in children after open reduction with K. wire fixation versus closed reduction with K. wire fixation - Talaat Othman, Mohammed; Muhammed Sleman Alany, Abdulkadr (Zanco Journal of Medical Sciences (ZJMS), 2024)
Background and objective: commonest fracture of pediatric elbow is the fractures of supracondylar of humerus. Gartland type II and type III Management is preferably operation, either with closed reduction and K. wire pinning or with open reduction and K. wire fixation. Some of the patients will get post-operative complications including Malunion. The aim of this study is to sort out the incidence of malunion in management of fractures of supracondylar in children by closed reduction and K. wire pinning versus open reduction-lateral approach and K. wire pinning. Methods: Forty nine children were included, who had Gartland type II and Type III Supracondylar fractures and underwent operative management, been enrolled using convenient sampling method. Patients are followed up after 12 weeks. During the review, assessment of the patient done for possible complications postoperatively and measured any possible change of degrees of carrying angle and movement loss at the elbow considering malunion complication. Results: 12% of the patients who are treated with close reduction and K. wire pinning developed malunion, while none of the patients who are treated with open reduction-lateral approach and K. wire pinning developed malunion. Conclusion: Incidence of malunion after treatment of supracondylar fracture of humerus in children with close reduction and K. wire pinning is more than the incidence by open reduction-lateral approach and K. wire pinning.